A longitudinal assessment of alcohol intake and incident depression: the SUN project - Gea Alfredo; Martinez-Gonzalez Miguel A; Toledo Estefania; Sanchez-Villegas Almudena; Bes-Rastrollo Maira; Nuñez-Cordoba Jorge M; Sayon-Orea Carmen; Beunza Juan J (BMC, 2012)
Abstract Background Longitudinal studies assessing the long-term association between alcohol intake and depression are scarce. The type of beverage may also be important. Therefore we aimed to prospectively evaluate the influence of alcohol intake on incident depression in a Mediterranean cohort. Methods We assessed 13,619 university graduates (mean age: 38 years, 42% men) participating in a Spanish prospective epidemiological cohort (the SUN Project), initially free of depression. They were recruited between 1999-2008 and biennially followed-up during 2001-2010. At baseline, a 136-item validated food-frequency questionnaire was used to assess alcohol intake. Wine was the preferred beverage. Participants were classified as incident cases of depression if they reported a new clinical diagnosis of depression by a physician and/or initiated the use of antidepressant drugs. Cox regression and restricted cubic splines analyses were performed over 82,926 person-years. Results Only among women, an U-shaped relationship between total alcohol intake and depression risk was found (P=0.01). Moderate alcohol intake (5-15 g/day) was associated with lower risk (Hazard Ratio: 0.62; 95% Confidence Interval: 0.43-0.89). No association was apparent for higher intakes of alcohol or for any specific type of alcoholic beverage. Conclusions Moderate alcohol intake might protect against depression among women. Further confirmatory studies are needed.